Analisis faktor-faktor yang mempengaruhi kinerja sistem informasi akuntansi pada Perusahaan Perhotelan yang ada di Riau dan Sumatera Barat - Dalimunthe, Ronna Wati; Agusti, Restu; Fitrios, Ruhul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine the effect of user involvement information system (XI), top management support (X2), the formalization of the information system development (X3), training and education (X4) and firm size (X5) on the performance of AIS (Y). the object under study is 3,4 and 5 star htel area Riau and West Sumatra with a total sample of 28 companies. This study user primary data, by distributing questionnaires to a sample company, before the questonnary were distributed, first tested the validity and reability testing. The analytical method used is multiple regression analiysis. Before testing the hypothetis, the data must first be tested by testing the normality of the data and the assumptions of classical studies to ensure that the data are free from bias/ambiguous. Based on the analysis, it is known that the independet variables have a significant influence on the performance of AIS (Y) is top management support (X2) and the training and education (X4). Meanwhile, the involvement of users (X1), the formalization of the information system development (X3) and firm size (X5) had no effect on the performance of AIS (Y). the coefficient of determination is 0,507 wich shows that 50,7 % of performance of AIS changes influenced by the determinant variables used in the model study while the rest (49,3%) is explained by other variables.Keywords : SIA Performance, User Involvement Information Sytem, Top Management Support, a formalization System Development, Training and Education, Company Size.